PENGARUH KUALITAS PELAYANAN DAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN DI PT. EKADHARMA INTERNATIONAL TBK CABANG BATAM - Arianto, Deddy; Rustam, Triana Ananda (SCIENTIA JOURNAL, 2021)
The purpose of this research is to find out how the influence of service quality and distribution on purchasing decisions at PT Ekadharma International Tbk Batam Branch with saturated sampling techniques that are all existing customers so as to get a sample number of 120 respondents. The method of collecting data is by a questionnaire that is distributed directly. Data quality test in this study using validity test and reliability test, classic assumption test and influence test in this study using multiple linear regression analysis and coefficient of determination (R2) analysis, while hypothesis test in this study using (t test) and (F test) using SPSS program software version 26. The result of coefficient of determination (R2) obtained is the variable quality of service and distribution affects 74.6% of purchasing decisions. from the results of t and f tests, it can be concluded that partially the quality of service and distribution has a significant effect on purchasing decisions, as well as simultaneously the quality of service and distribution have a significant effect on purchasing decisions.